The Perceived Usefulness of Gamified E-Learning: A Study of Undergraduate Students With Implications for Higher Education - Aguilos, Veronica; Fuchs, Kevin (Frontiers in Education, 2022)
Gamification is about applying gaming strategies and game elements to improve learning, and thus, making it more engaging for individuals. The application of gamification in higher education aims to incentivize students and is said to improve the efficiency of self-paced learning. The study aims to explore the perceived usefulness and challenges of gamified learning in the context of a massive open online course. A qualitative exploratory study design was adopted to collect empirical data from 19 undergraduate students about their experiences with gamified learning. An inductive approach was used to interpret the results thematically. A total of four themes emerged from the data analysis. The collected data revealed that students’ competitive behavior has a significant effect on students' marks in the activities. Moreover, instant gratification from immediate feedback and evaluation was perceived as highly motivating for the students. The article concludes by presenting implications for educators, policymakers, and education researchers derived from the academic and practical discussions based on the findings.